The Lote para sa Mahihirap Housing Program of San Carlos City, Negros Occidental - Estela F. Paredes; Anicia C. Sayos (Philippine Institute for Development Studies (PIDS), 1998)
With the passage of the Local Government Code in 1991, LGUs are challenged to efficiently manage its resources given the responsibility of delivering basic services. With this premise, the "Population and Urbanization: Managing the Urbanization Process Under a Decentralized Governance Framework ", a joint project of the National Economic and Development Authority, Philippine Institute for Development Studies and Development Academy of the Philippines, has attempted to look at the means and strategies of some LGUs in handling the problems caused by rapid urbanization in fiscal/environmental management, health and housing sectors. This paper highlights the best practices of LGUs. In particular, it focuses on the innovative ideas of San Carlos City in Negros Occidental in solving the city's squatting problem.
Keywords: 330; governance; housing program; fiscal management; urbanization